2004
DOI: 10.1177/0038038504040867
|View full text |Cite
|
Sign up to set email alerts
|

(Inter)Dependence, Needs and Care

Abstract: In this article we examine the tensions between feminist and disability studies perspectives on care.We argue that an emancipatory model of care is one that must address these tensions. In developing this model we consider the notions of (inter)dependence and need across the lifecourse. Drawing on the work of Fraser (1989), we propose that the notion of ‘needscape’ can be used to construct a ‘discourse bridge’ that will mediate between the disability studies and feminist perspectives on care. Notions of care a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(14 citation statements)
references
References 23 publications
(29 reference statements)
0
10
0
4
Order By: Relevance
“…Being a recipient of care can also be conceptualized as being a passive object under the control and power of the one‐caring (Silvers 1998). The cared‐for is understood as a burden, a recipient of the commendable efforts of the carer: “For every self‐sacrificing martyr, there is a parasite benefiting from the charitable nature of a heroic carer” (Watson et al 2004, 336) 14 . In order to overthrow this image, acquire control over the situation and status as an active participant in the caring relationship, disability organizations have sought to substitute the term care with personal assistance or help .…”
Section: The Altruistic Understanding Of Carementioning
confidence: 99%
See 2 more Smart Citations
“…Being a recipient of care can also be conceptualized as being a passive object under the control and power of the one‐caring (Silvers 1998). The cared‐for is understood as a burden, a recipient of the commendable efforts of the carer: “For every self‐sacrificing martyr, there is a parasite benefiting from the charitable nature of a heroic carer” (Watson et al 2004, 336) 14 . In order to overthrow this image, acquire control over the situation and status as an active participant in the caring relationship, disability organizations have sought to substitute the term care with personal assistance or help .…”
Section: The Altruistic Understanding Of Carementioning
confidence: 99%
“…In order to overthrow this image, acquire control over the situation and status as an active participant in the caring relationship, disability organizations have sought to substitute the term care with personal assistance or help . In doing so the emotional aspect of care is downplayed, and the focus is on the practical work, over which the disabled person can achieve some measure of control (Watson et al 2004). On the theoretical level, one can explain the different understandings of care, on the one hand as understood by the disability organizations, and on the other hand as described in an ethics of care, by reference to differences in their respective moral ontologies.…”
Section: The Altruistic Understanding Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…Sameiginlegur flötur fötlunarfraeðinga og femínista felst í að líta á samband aðstoðarfólks og þjónustunotenda sem fjölþaett. Viðurkenna þarf gagnkvaem tengsl og gagnkvaemar þarfir og það að báðir aðilar eru háðir hvor öðrum í flóknu samspili (Walmsley, 1993;N. Watson, McKie, Hughes, Hopkins og Gregory, 2004).…”
Section: Gagnkvaemni í Aðstoðunclassified
“…Although care is commonly meant to be a 'good thing', receiving care may actually be experienced as oppressing, whereby care-recipients are subject to over-protection and control (Bondi 2008;Smith 2016). Nursing and disability scholars have shown that giving and receiving care is often instilled with dependence, revealing a certain degree of acceptance of the role of being more or less capable (Russell, Bunting, and Gregory 1997;Shakespeare 2000;Wood 1991;Watson et al 2004). Inextricably bound up with human vulnerabilities and the connections thereby, caring relationships are emotionally complex and they reflect experiences of power dynamics (Bondi 2008;Locke 2017).…”
Section: Transnational Care-receiving In Transnational Social Protectmentioning
confidence: 99%